Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1007/s00125-020-05305-2
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxybutyrate inhibits histone deacetylase 3 to promote claudin-5 generation and attenuate cardiac microvascular hyperpermeability in diabetes

Abstract: Aims/hypothesis Microvascular endothelial hyperpermeability, mainly caused by claudin-5 deficiency, is the initial pathological change that occurs in diabetes-associated cardiovascular disease. The ketone body β-hydroxybutyrate (BHB) exerts unique beneficial effects on the cardiovascular system, but the involvement of BHB in promoting the generation of claudin-5 to attenuate cardiac microvascular hyperpermeability in diabetes is poorly understood. Methods The effects of BHB on cardiac microvascular endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…Secondly, we addressed the possibility whether D‐β‐hydroxybutyrate would exert its functions by inhibiting class I histone deacetylases (HDAC) as this has been shown by treating mice with high doses (Shimazu et al , 2013 ). In ECs, there are contradictory reports about the efficiency of D‐β‐hydroxybutyrate acting as a HDAC inhibitor (Chriett et al , 2019 ; Li et al , 2021 ). To rule out the possibility that increased angiogenic potential of MCEC would merely be the consequence of HDAC inhibition, MCEC were treated with the well‐established HDAC inhibitor butyrate (Shimazu et al , 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, we addressed the possibility whether D‐β‐hydroxybutyrate would exert its functions by inhibiting class I histone deacetylases (HDAC) as this has been shown by treating mice with high doses (Shimazu et al , 2013 ). In ECs, there are contradictory reports about the efficiency of D‐β‐hydroxybutyrate acting as a HDAC inhibitor (Chriett et al , 2019 ; Li et al , 2021 ). To rule out the possibility that increased angiogenic potential of MCEC would merely be the consequence of HDAC inhibition, MCEC were treated with the well‐established HDAC inhibitor butyrate (Shimazu et al , 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…It can bind to the G protein-coupled receptor GPR109A and activate the AMPK signal pathway to exert anti-inflammation effects and prevent the endoplasmic reticulum (ER) stress response and lipid accumulation [ 25 ]. BHB treatment can inhibit HDAC3 to promote claudin-5 generation and antagonize diabetes-associated cardiac microvascular hyperpermeability [ 50 ]. In addition, BHB can inhibit the activation of NLRP3 inflammasome, which is independent of GPR109A-mediated signaling, HDAC3, autophagy, or other starvation-regulated mechanisms [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…BHB was found as a competitive inhibiting catalytic site, directly inhibiting class I histone deacetylases (HDACs) ( 83 ), which were thought to participate in the regulation of gene expression by deacetylating lysine residues on histone and nonhistone proteins, such as NF-κB, TP53, MYC, and MYOD1 et al., and consequently regulates corresponding gene expression ( 84 , 85 ). Li and colleagues found that BHB upregulated claudin-5 gene expression and ameliorated the diabetes-associated cardiac endothelial hyperpermeability by inhibiting HDAC3 ( 60 ) ( Figure 2A ). By lysine β-hydroxybutyrylation, BHB can also directly modify proteins in multiple model organisms, including yeast, fly, rat, and human cells, and regulates gene expression ( 63 ).…”
Section: Energy and Signal Roles Of Bhbmentioning
confidence: 99%